Calculation Model to Predict the Static Armor Layer Size Distribution After the Reconstruction of a Gravel River Bed - Wang, Qiang; Li, Like; Li, Xinjie; Wang, Yuanjian; Nie, Ruihua (Frontiers in Earth Science, 2021)
The size distribution of armor layer in mountain rivers is an important factor that affects the stability of the river bed. However, there are relatively few studies on the prediction of armor layer size distribution in the reconstruction process after the previous static armor layer becomes unstable. In response to the above challenges, this study considers the incipient probability of sediment particles as the starting point, and comprehensively considers the coupling relationship between the initial bed materials, bed structure, armor ratio, and flow intensity, using a simple calculation model for predicting the static armor layer size distribution after reconstruction of a gravel-river bed. This paper introduces the concept of critical incipient particle size Dc, and considers that sediment particles smaller than Dc will incipient easily, resulting in a higher probability of being washed out, whereas the incipient probability of sediment particles larger than Dc (this part of the large-particle sediment includes not only the original particles on the bed surface, but also the large sediment particles exposed by the erosion of the bed subsurface) is relatively small. At the same time, this model also uses the armor ratio to reflect the impact of the bed surface structure. This study cites data from five sets of laboratory flume experiments to verify the calculation model, and the experimental results show that the model calculation results are in good agreement with the experimentally measured data, especially in predicting the median diameter D50 of the static armor layer. Our calculation model provides theoretical guidance for the study of mountain riverbed stability, earthquake prevention and disaster reduction.